2020
DOI: 10.1002/uog.21909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biometric measurement error on identification of small‐ and large‐for‐gestational‐age fetuses

Abstract: CONTRIBUTION What are the novel findings of this work?This study examines the impact of measurement errors in fetal head circumference, abdominal circumference and femur length on sonographic estimated fetal weight (EFW) and their effect on the prediction of small-(SGA) and large-(LGA) for-gestational-age fetuses.What are the clinical implications of this work? Measurement error in fetal biometry causes substantial error in EFW, resulting in misclassification of SGA and LGA fetuses. The extent to which impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Classification of growth disorders is also affected by errors in biometric measurements in EFW assessment 31 . The consequence of these measurement errors can also be seen on a percentile chart; the position of a measurement on a percentile chart is shifted horizontally by errors in gestational age that originate from errors in CRL.…”
Section: Found That Operator-specific Pregnancy-associated Plasma Protein-a (Papp-a) Multiples Of the Median Valuesmentioning
confidence: 99%
“…Classification of growth disorders is also affected by errors in biometric measurements in EFW assessment 31 . The consequence of these measurement errors can also be seen on a percentile chart; the position of a measurement on a percentile chart is shifted horizontally by errors in gestational age that originate from errors in CRL.…”
Section: Found That Operator-specific Pregnancy-associated Plasma Protein-a (Papp-a) Multiples Of the Median Valuesmentioning
confidence: 99%
“…Previous studies have demonstrated that large systematic differences of mean NT or NT scatter can significantly influence the SPR of individual sonographers 6 . Using theoretical modelling it was recently demonstrated that measurement variation in HC, FL, and AC could cause similar error in EFW and consequent misclassification of SGA and LGA fetuses 15 . We tested this approach within an established service offering universal ultrasound for SGA detection.…”
Section: Discussionmentioning
confidence: 99%
“…27 Wright et al concluded that errors in individual fetal measurement cause substantial errors in EFW, resulting in misclassification of small and large-for-gestational ages fetuses. 28 In interpreting EFW measurements in the context of fetal growth, it is important to understand and acknowledge these errors since many obstetric decisions such as timing and mode of delivery are based on EFW. Figure 1 shows that EFW centiles on the INTERGROWTH-21st chart are lower than those on the Hadlock et al, WHO and FMF charts.…”
Section: Discussionmentioning
confidence: 99%